The Relationship Between Locus of Control and Students Performance: Systematic Literature Review (SLR) - Trimastuti, Wahyu; Fitriani, Sri Wuli; Astuti, Puji (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The teacher plays an important role in the world of education; it is preparing students to become individual who have skills in cognitive engagement and academic performance to face life's challenges in the future. For anticipating that issue in the globalization era, students should be prepared with the competence related to their department which is supported by their competence. In carrying out their duties as teachers, it is appropriate for teachers to understand student needs to increase their capability. The term locus of control refers to how individuals tend to explain their successes and failures. Providing appropriate treatment in teaching is expected to be able to support the performance of students in their success. This research was conducted to examine the effect of locus of control on students’ performance particularly in English Language Teaching (ELT) which was carried out using the SLR (Systematic Literature Review) method, namely by identifying, reviewing, evaluating, and interpreting all previous studies that were closely related to teacher compensation and performance. Using the PRISMA protocol, this study conducted three stages of rigorous and systematic searching: identification, screening, and eligibility. As a result of the search, this study identified 6 relevant articles from Scopus, Web of Science, and ScienceDirect as the leading databases and Google Scholar and Dimension. ai as supporting databases. This study provides an insight for integrating psychological concept in ELT. The review concluded that locus of control has impact for students’ performance in ELT. Students who have internal locus of control more responsible in their performance to get good performance than students who have external locus of control.